2018
DOI: 10.1002/adom.201800201
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Optical Amplifier–Photodetector on a Wearable Nanocellulose Substrate

Abstract: Moreover, the implementation of a wearable photonic technology directly in contact with clothes would be light-weight, comfortable, noninvasive, implantable, and inherently low cost. It attracts a strong interest for industry in this futuristic field. Indeed, according to International Data Corporation, the important growth of this technology is forecasted to grow up to 213.6 millions in 2020. [8] Nowadays, examples of commercial real-time applications include textile-based displays, [9] photovoltaics [9] or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Apart from polymer, paper, and fiber, there are some other materials used as substrates for wearable PDs such as silicon, mica, etc …”
Section: Materials and Architecture Design Of Wearable Pdsmentioning
confidence: 99%
“…Apart from polymer, paper, and fiber, there are some other materials used as substrates for wearable PDs such as silicon, mica, etc …”
Section: Materials and Architecture Design Of Wearable Pdsmentioning
confidence: 99%
“…For this purpose, we investigate the evolution of the PL spectra with the extication fluence of polycrystalline layers of MAPI integrated in polymer planar waveguides. We have already demonstrated that this configuration is an optimal one for ASE, because it provides a long path for the emitted photons and highly confines the optical modes of the photonic structure [11,12]. Here, we establish how the geometrical parameters influence the behavior of the waveguide to minimize the ASE threshold.…”
Section: Introductionmentioning
confidence: 78%
“…Indeed, from the earliest publications with CH 3 NH 3 PbI 3 (MAPI) polycrystalline thin films [9] MHPs have exhibited exceptional optical-gain performances in the visible and near-infrared wavelength range [10]. Low thresholds (1-10 nJ/cm 2 ) of stimulated emission under pulsed excitation were demonstrated in several publications by incorporating perovskite layers into waveguides [11,12], optical resonators [13][14][15], or by synthetizing this material as microdisks [16][17][18] and nanowires [19,20]. More recently, lasing operation in MAPI films under continuous-wave operation was demonstrated [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Perovskites can be divided into organic-inorganic halide perovskites following the structure ABX 3 (Figure 7a), where A is an organic cation, B is a metal cation and X is an halide anion, or inorganic only halides [272,273]. In flexible sensors, these materials have been mostly employed as active materials in photodetectors, prevalently in the form of organic-inorganic methilammonium lead bromide/iodide/chloride (CH 3 NH 3 PbX or MAPbX) [18,29,272,[274][275][276][277][278][279][280][281], and inorganic caesium lead bromide (CsPbBr 3 ) [282][283][284][285], or as piezoelectric materials such as PbZr x Ti 1-x O 3 (PZT) on ultrasound sensors [286]. The application and development of these materials for flexible optoelectronic applications has been widely researched due to their optical and electrical properties.…”
Section: Black Phosphorusmentioning
confidence: 99%